Where to work? Gender differences in labor market outcomes during economic crisis - Ralitza Dimova; Ira N. Gang; John Landon-Lane (Osteuropa-Institut Regensburg, 2011)
In Central and Eastern European women started the process of transition from socialist to market economies with a status quo that differed markedly from women in both developed western and traditional developing economies. They enjoyed an equal or higher level of education than men, virtually no unemployment, only temporary labor force departures, lavish maternity and child related benefits. Using panel data constructed from the 1995 and 1997 Bulgarian Integrated Household Surveys, our results reveal striking gender differences with respect to the reallocation of male and female employ-ees to and out of the public and private sectors.
Keywords: J21; J23; J31; J62; P2; 330; Employment; Mobility; Gender; Household; Weibliche Arbeitskräfte; Übergangswirtschaft; Wirtschaftskrise; Arbeitsmobilität; Geschlechterdiskriminierung; Bulgarien